Interrogating informality: Conceptualisations, practices and policies in the light of the New Urban Agenda. (May 2018) - Alfaro d'Alençon, Paola; Smith, Harry; Álvarez de Andrés, Eva; Cabrera, Cecilia; Fokdal, Josefine; Lombard, Melanie; Mazzolini, Anna; Michelutti, Enrico; Moretto, Luisa; Spire, Amandine
Abstract: Informality is growing in a context of increasing inequity, and in many places becoming the norm. However, despite decades of studies and interventions, 'recognising informality' is still a key issue. This paper provides a review of the literature on informality showing the shifts in its conceptualisations. The paper firstly discusses conceptual approaches related to the term 'informality' in the context of urban development; it then examines practices within, and related to, informality; and it concludes with an appraisal of policy approaches and their impact as reported in the literature. The paper finds a wide range of conceptualisations, including the questioning of the usefulness and appropriateness of the term. It finds reported evidence of 'informality' (as understood to date) spreading to the middle classes, and increasingly emerging in the Global North. Policies seem to be lagging behind in how they engage with so-called informality, with little acknowledgement of theory and limited understanding of their impacts on 'informal' practices. Finally, the paper identifies the need for better understanding of governance frameworks that include the range of actors that would normally be associated with so-called 'informality'. Highlights: This paper questions the usefulness and appropriateness of the term 'informality' in urban debates. It reflects on actors and underlying mechanisms while analysing theory, practices and policies related to the concept. It shows that informality (as understood to date) is spreading to the middle classes and the Global North. Policies are generally lagging behind theory in how they engage with so-called informality. We need urban governance frameworks that include actors 'normally' associated with 'informality'.